Evaluation of Three Working Fluid on an Organic Rankine Cycle of a Waste Heat Recovery Electric Generator - Margana, Lazuardi; Sirodz Gaos, Yogi; Mulyo Utomo, Wahyu; Sukri Mustapa, Mohammad; Muliawati, Fithri; Afrianto, Yuggo; Br Ginting, Novita (International Journal of Integrated Engineering, 2022)
The aim of this study is to evaluating an Organic Rankine Cycle (ORC) system from diesel engine waste heat recovery by selecting three different working fluids with different pressure and temperature condition. N-Pentane, R-245fa, and R-134a are conditioned on variations in pressure and evaporation temperature with a difference of 0.5 bar and 5 Â°C from the previous best practice to achieve the best thermal efficiency. The proposed evaluation involved two phases, first is analysis of the working fluid with various condition is carried out using REFPROP software and then results of that analysis will be used as the basis of input in calculating the overall heat balance using the Cycle Tempo software. This study found that a diesel engine with a capacity of 1000 kVA wastes energy of 1177 kW which is released through exhaust pipe and engine radiator can produce a turbine power of 144,47 kW. The highest thermal efficiency of 13.48% was obtained by using the working fluid R-245fa at the evaporator pressure and temperature of 23.5 bar and 154 â°C, respectively.